Comparison of phenolic constituent in Hibiscus sabdariffa cv. UKMR-2 calyx at different harvesting times - Siti Aishah Mohd Ali; Che Radziah Che Mohd Zain; Jalifah Latip (Penerbit Universiti Kebangsaan Malaysia, 2019)
The metabolic changes in the phenolics content of Hibiscus sabdariffa cv. UKMR-2 were investigated at different harvesting times based on the High-Performance Liquid Chromatographic method using a photodiode array detector (HPLC-PDA) with gradient elution. The antioxidant activity was also determined using 2,2-diphenyl-1-picrylhydrazyl free radical scavenging activity (DPPH) assay. The cultivation was executed under a control condition, and the calyces were separately harvested at four maturation stages. UKMR-2 calyces were extracted with water via sonication (50°C, 30 min). HPLC-PDA analysis showed two predominant anthocyanins, namely delphinidin-3-O-sambubioside (2.07-2.47 mg/g DW) and cyanidin-3-O-sambubioside (0.55-1.01 mg/g DW). In addition, ascorbic acid (3.34-9.88 mg/g DW), caffeic acid (0.08-0.09 mg/g DW) and chlorogenic acid (0.50-0.65 mg/g DW) were also detected in all maturity stages. Cyanidin-3-O-sambubioside content increased as the calyx became more mature, whereas the delphinidin-3-O-sambubioside, ascorbic acid, and chlorogenic acid content declined towards calyx maturity. The antioxidant activity gradually increased as the calyx ripening progressed. However, the activities did not differ significantly between the stages (p>0.05). The high content of total phenolic, total anthocyanins, and free radical scavenging activity were detected at Stage 4 (28-30 DAA) in UKMR-2, suggesting that this stage is the most appropriate maturity stage for harvesting H. sabdariffa cv. UKMR-2 calyces compared to the other maturity stages.